Pengaruh Personal Branding dan Sistem Pembayaran Digital Terhadap Keputusan Pembelian (Mansion: Management and Business on Kebangsaan, 2025)
Introduction: The expansion of digital technology has transformed consumer behavior and purchasing decisions, particularly in the food and beverage sector. This study focuses on Menantea, a brand cofounded by public figure Jerome Polin, to explore how personal branding and digital payment systems influence consumer purchase decisions. Background Problems: Despite the popularity of digital platforms, many consumers still rely on cash transactions, prompting the research question: Do personal branding and digital payment systems significantly affect consumers’ purchase decisions at Menantea in Bandung? Novelty: While prior studies have discussed branding and fintech adoption separately, limited research has investigated their combined influence within the Indonesian retail beverage industry, particularly when associated with a well-known influencer. This study addresses that gap. Research Methods: A quantitative approach was applied, utilizing incidental sampling to survey 96 respondents familiar with Menantea. Data were collected via online questionnaires and analyzed through multiple linear regression using SPSS 25. Finding/Results: The results indicate that both personal branding and digital payment systems positively and significantly affect purchasing decisions. Personal branding has a stronger influence (β = 0.523) compared to digital payments (β = 0.398), with a combined determination coefficient (R²) of 64.9%. Conclusion: The study concludes that both personal branding and digital payment efficiency are strategic levers in driving customer purchase behavior. These insights are particularly useful for businesses leveraging influencer-based marketing and tech-driven payment innovation.
Keywords: digital payment systems; purchasing decisions; personal branding